Islam and Transgender (A Study of Hadith about Transgender) - Muh. Bahrul Afif (International Journal of Nusantara Islam, 2019)
One of the issues that have been considered in the public sphere today is the issue of the transgender phenomenon. Transgender is related to the problem of gender identity. It refers to the condition in which the perpetrators identify their identity and gender differently from their sex biologically. It's caused by dissatisfaction and incompatibility between their body and soul. The term transgender might not be so familiar in Indonesia. However, to indicate that phenomenon, some of the people called them "waria”, “priawan” or “tomboy". Generally, their existences were still hard to be accepted because Indonesian people considered this phenomenon as a deviation and it contradicts the moral value and religion in Indonesian society. In the teachings of Islam, the transgender phenomenon has been existed in the early days of the development of Islam, and it has been forbidden strictly. The Islamic view about this issue could be found in the prophet’s hadith explicitly. Hence, to understand this phenomenon, we need to study the hadith. The purpose is as a basis for addressing the transgender phenomenon that was prevalent in Indonesia. The understanding implementation of this hadith, in general, is not easy, because Indonesia is not a country that makes Islam as a formal state system. It has its perspective relate to the transgender phenomenon. Therefore, we have to contextualize this hadith understanding according to the Indonesian context, especially in dealing with transgender perpetrators.